2006
DOI: 10.1079/bjn20051628
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the behaviour of oil-in-water emulsions in the gastric lumen of man

Abstract: Pre-processed foods often contain a high percentage of lipid, present as emulsions stabilised with various surface-active agents. The acidic gastric environment can affect the behaviour of such emulsions, modifying the lipid spatial distribution and, in turn, the rate of gastric emptying and nutrient delivery to the gut. The aim of the present study was to use echo-planar magnetic resonance imaging (EPI) to determine the behaviour of model olive oil emulsions during gastric processing. Six healthy male volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
57
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 34 publications
7
57
1
1
Order By: Relevance
“…After preparation, the emulsion samples were left to equilibrate for 15 min in a 37°C water bath while being slowly stirred with a laboratory ministirrer. Our previous studies (34) showed that although both emulsions had the same initial mean oil droplet size (3.6 m), after acidification the acid-unstable one had no remaining oil droplets with complete separation of oil and water layers whereas the acid-stable emulsion particle size distribution was unchanged.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After preparation, the emulsion samples were left to equilibrate for 15 min in a 37°C water bath while being slowly stirred with a laboratory ministirrer. Our previous studies (34) showed that although both emulsions had the same initial mean oil droplet size (3.6 m), after acidification the acid-unstable one had no remaining oil droplets with complete separation of oil and water layers whereas the acid-stable emulsion particle size distribution was unchanged.…”
Section: Methodsmentioning
confidence: 99%
“…The volunteers were fed 500 ml of the olive oil-in-water emulsion test meals that we have characterized previously both in vitro and in vivo (34,35). They have equal fat content (hence equicaloric, 675 kcal) and equal lipid droplet size distributions, but opposite acid stability.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations